Characteristics of the Relationship of Kidney Dysfunction with Cardiovascular Disease in High Risk Patients with Diabetes - Attilio Losito; Loretta Pittavini; Ivano Zampi; Elena Zampi (International Journal of Nephrology)
We aimed at comparing the relationship of reduced estimated glomerular filtration rate (eGFR) with cardiovascular disease (CVD) and mortality between high risk patients with and without type 2 diabetes mellitus (T2DM). The cross-sectional study evaluated 16,298 participants (1,627 T2DM) acutely admitted to hospital. The longitudinal study comprised 7,508 patients (673 with diabetes and 6,835 without). eGFR was categorized into 6 stages from >90 to <15 mL/min/1.73 m2. Kidney dysfunction was defined by an eGFR < 60 mL/min/1.73 m2. Patients with T2D showed a higher prevalence of CVD (37.9% versus 23.6%; P<0.001) and kidney dysfunction (25% versus 13.2%; P<0.001) than in the general population. An association with CVD was found with eGFR stages from 30 to 90 mL/min/1.73 m2 in T2D and from <15 to 90 mL/min/1.73 m2 in general population, in whom the association of eGFR with coronary heart disease was in an inverse relationship (P<0.01 for trend). Survival, in diabetes, was lower (P=0.037) but not associated with kidney dysfunction. Conclusions. In a high risk population, patients admitted to hospital, the relationship of kidney function with CVD is different between T2D and the general population. Competing mortality and the presence of other major risk factors in diabetes may be responsible for this difference.